Management of Anal Fistula with Crohn's Disease - Shota Takano; Yasushi Nakamura; Kohei Tamaoka; Takafumi Yoshimoto; Yasue Irei; Yoriyuki Tsuji (Journal of the Anus, Rectum and Colon)
Crohn's disease (CD) causes gastrointestinal symptoms (i.e., diarrhea and abdominal pain), systemic symptoms (i.e., fatigue, anemia, weight loss, and fever), and perianal fistulas that produce anal pain. Because of the frequent occurrence of diarrhea and ulcers in the rectum, CD is often exacerbated by perianal abscesses and/or fistulas. Perianal fistulizing CD (PFCD) has an unknown etiology and recurring symptoms such as pain and discharge, which seriously affects the patient's quality of life (QOL). In the past, radical surgery was performed for PFCD, but due to the risk of anal sphincter impairment, conservative therapy using antibiotics and immunosuppressive medications is currently the first treatment option. PFCD management has greatly improved with the use of biologics such as the antitumor necrosis factor alpha (TNF-α) antibodies infliximab and adalimumab. In this review, the results of the administration of anti-TNF-α (certolizumab pegol), anti-interleukin-12/23 (ustekinumab), and anti-α4β7 integrin antibodies (vedolizumab) were evaluated. Our investigation showed that these medications may be effective for maintenance therapy to prevent the recurrence of anal fistulas. In addition to biologics, molecular target drugs and even regenerative medicine using mesenchymal stem cells have been introduced to further expand the treatment options for consideration by medical personnel. We herein discuss the management of PFCD by focusing on studies conducted in the United States and Europe where researchers used recommended guidelines and consensus statements to evaluate the efficacy of each medication and published their findings in peer-reviewed journals.